Application of Color Code Music Notation in Learning Piano for Early Childhood - Putra, Zakarias Aria Widyatama (GENIUS: Indonesian Journal of Early Childhood Education, 2024)
Introducing piano instruments to young children can significantly enhance their cognitive and academic development. This study delves into the effectiveness of using "Buku Musikku/My Music Book," a resource created by Yuniasri Maya Aisyah, specifically designed to teach preschoolers tone notation using color codes. A qualitative research approach was employed, focusing on a music course house in Pontianak City, Indonesia. Data was gathered through participant observation, interviews, and documentation, and its validity was ensured through source triangulation. The interactive model of Miles and Huberman was used to analyze the data. The study examined how color-coded music notation on piano instruments can aid early childhood understanding of fundamental musical elements: rhythm and melody. The rhythm section utilized fruit-shaped objects to visually represent beat values, while the melody section focused on matching color codes to specific note targets. The key finding of this research is that color-coded tone notation can indeed help young pianists recognize notes more effectively, making it a valuable tool for early childhood music education.